Reduced Risk of Atrial Fibrillation Following Cholecystectomy: A Nationwide Population-Based Study - Ho, Tung Ching; Chen, Yu-Ching; Lin, Che-Chen; Tai, Hsu-Chih; Wei, Cheng-Yu; Yeh, Yung-Hsiang; Hsu, Chung Y. (Frontiers in Aging Neuroscience, 2021)
Background: Gallstone disease (GD) is associated with a high risk of cardiovascular disease. However, it is unknown whether GD contributes to atrial fibrillation (AF). We aimed to investigate the association between GD and AF. Methods: We performed a population-based cohort study using data from the Taiwan National Health Insurance Research Database between 2001 and 2011. A GD cohort of 230,076 patients was compared with a control cohort consisting of an equal number of patients matched for age, sex, cardiovascular and gastrointestinal comorbidities. Results: In total, 5,992 (49.8/10,000 person-years) patients with GD and 5,804 (44.5/10,000 person-years) controls developed AF. GD increased AF risk with a hazard ratio (HR) of 1.20 (95% confidence interval [CI], 1.16-1.25). In patients with GD but without cholecystectomy, the HR of AF reached 1.57 (95% CI = 1.50-1.63). After cholecystectomy, the HR of AF significantly decreased to 0.85 (95% CI = 0.81-0.90). Among the three age groups with GD (<45, 45-64, and ≥65 years), the adjusted HRs of AF were 1.59 (95% CI = 1.08-2.33), 1.31 (95% CI = 1.18-1.45), and 1.18 (95% CI = 1.13-1.22), respectively. Compared with patients with a CHA2DS2-VASc score equal to 0, the HRs of AF risk among total cohort patients and a score equal to 1, 2, 3, and 4 were 1.28 (95% CI = 1.15-1.43), 2.26 (95% CI = 2.00-2.56), 3.81 (95% CI = 3.35-4.34), and 5.09 (95% CI = 4.42-5.87), respectively. Conclusion: This population-based longitudinal follow-up study showed that patients with GD had an increased AF risk. Moreover, cholecystectomy was related to reduce AF risk. Cardiovascular checkup may be necessary for patients with GD, especially those who are young and have other typical risk factors.